Antagonism or Synergism effect of heavy metals (Cadmium and Lead)upon growth of green alga Chlorella vulgaris - Hussain Yousif Al-Rekabi (Al-Qadisiyah Journal of Pure Science, 2017)
The antagonism or synergism effect of some heavy metals (both Cadmium and Lead) indifferent concentrations upon growth of green alga Chlorella vulgaris were studied, firstly,the effect of each metal alone was carried out by adding the cadmium metal (0.1 , 0.5, 1, 2, 3)mg/L to culture, the concentration (3 mg/L) was more toxicity for alga, and the lowestchlorophyll content was in second day (1.9) Î¼g/100 ml in comparison with control(2.4Î¼g/100 ml). For the Lead ,was added as(30 ,40, 50, 75 and 100) mg/L, and the concentration(100 mg/L)was more toxicity for alga and the chlorophyll content reduced to (1.6) Î¼g/100ml in comparison with control.In the other experiments , metal ions were mixed and added together to the culturemedia as concentrations (30 Pb + 0.1 Cd ; 40 Pb + 0.5 Cd and 50 Pb + 1 Cd) mg / l , theconcentration (30 Pb + 0.1 Cd) was the lowest toxicity, and recorded the maximum of dryweight which reached to(63.3) mg/gm in C. vulgaris and chlorophyll content (11.5 Î¼g/100ml ) . Some cases of antagonism effect were happened depending on used concentration andexposure period , and the growth rates were increased , while the doubling time weredecreased.